A SPEECH ERRORS/ TONGUE SLIPS PADA MASA USIA DINI - Yus, Anita (Kajian Linguistik dan Sastra, 2012)
The purposes of this study are to obtain information related to speech errors forms or tongue slips of the children, to describe the time and condition in which the tongue slips occurs, and to know the response given by the environment toward the tongue slips above. This research was done in the family that has a child who gets difficulty in doing verbal communication, however, he is easy to make self adaptation well with situation and condition that he faces. The results of the research show that first the child gets difficulty in verbal communication in the form of tongue slips. Second, it occurs when the he got depression emotionally. It has not been done diagnosis by the expert whether the tongue slips has correlation with neurology or not. Third, the tongue slips developes quickly because he gets over responses from his environment (parents, nursemaid, and people around him) that finally make him gets more depression.